Extrusion printed polymer structures: A facile and versatile approach to tailored drug delivery platforms - Parawee Rattanakit (2018)
A novel extrusion printing system was used to create drug delivery structures wherein dexamethasone-21-phosphate disodium salt (Dex21P) was encapsulated within a biodegradable polymer (PLGA) and water soluble poly(vinyl alcohol) (PVA) configurations. The ability to control the drug release profile through the spatial distribution of drug within the printed 3-dimensional structures is demonstrated. The fabricated configurations were characterised by optical microscopy and SEM to evaluate surface morphology. The results clearly demonstrate the successful encapsulation of dexamethasone within a laminated PLGA:PVA structure. The resulting drug release profiles from the structures show a two stage release profile with distinctly different release rates and minimal initial burst release observed. Dexamethasone release was monitored over a 4-month period. This approach clearly demonstrates that the extrusion printing technique provides a facile and versatile approach to fabrication of novel drug delivery platforms. © 2011 Elsevier B.V.